Geochemical study of the Ashele Copper-Zinc Deposit using portable X-ray fluorescence spectrometry based on matrix effect correction, Northwest China. (November 2022) - Guo, Jinke; Lu, Jilong; Chen, Zesu; Zhao, Xinyun; Wei, Qiaoqiao; Fan, Yuchao; Lan, Tian
Abstract: Because the Ashele Cu–Zn deposit is located deep below and core samples are difficult to obtain, portable X-ray fluorescence spectroscopy (pXRF), which can be used for rapid and non-destructive analysis in the field, was chosen as the testing instrument. However, the testing accuracy and precision of elements are significantly affected by matrix effects. In this study, 170 samples from the deposit were measured, and the data was corrected using the matrix effect correction (MEC) method instead of the simple linear regression (SLR) method to enhance the data quality, followed by geochemical and correspondence analysis of the data. The results show that calibration data corrected by the MEC method was of greater quality than those corrected by the SLR method, particularly for elements such as Co, Cr, Mo, Sn, Ba, and W. The Ashele Cu–Zn deposit is formed in multi-phase hydrothermal superposition mineralization and is rich in Mg, Fe, and S but deficient in Al, Si, K, and Ca. The main mineralized zones are located at 400–500 m and 200–300 m. Cu, Zn, and Pb are significantly enriched in the mineralization, with the axial zoning sequence of the primary halo (Pb–Zn–Mn–As–Cu–Cd–Sn–Ba–Bi–Sb–Co–W–Mo) showing inverse zoning. The correspondence analysis results also show a clear distinction between non-metallogenesis and metallogenesis. Also, the application of pXRF based on MEC in the Ashele Cu–Zn deposit is effective and can be extended to other types of deposit studies. Highlights: The study of the Ashele deposit using portable X-ray fluorescence spectrometry. The data quality is improved by a new matrix effects correction method on pXRF. Using correspondence analysis instead of factor analysis to analyze variables.